Future IP network architecture evolution for service and network collaboration - Bing HUANG; Bin TAN; Jian LUO; Yong GUO (Dianxin kexue)
As the technical foundation of the internet, how IP technology develops in the next 5 to 10 years is the key issue facing the communication industry.The success and weakness of the traditional IP network architecture were analyzed, and the future IP network should not only inherit the design principles of the traditional IP technology was proposed, such as the end-to-end principle and layered decoupling principle, but also solve the problem that the service is too separated from the network.From the perspective of network evolution and future service requirements, the core issue of future IP networks is to strengthen the collaboration of between services and networks , and the improved IP network design principle “horizontal: end-to-end principle empowered by service-oriented network, vertical: layered model supported by intelligent control plane” was proposed, and based on this principle, the reference architecture of the future network was proposed.